AHP-Based Evaluation of the Suitability of Shallow Geothermal Energy Utilization in GSHP System - Dong, Jie; He, Peng; Liu, Honghua; Guan, Yong; Liu, Haisong; Xia, Weiqiang; Dong, Jierui (Frontiers in Energy Research, 2022)
Shallow geothermal energy (SGE) is a part of geothermal resources and is mainly used through ground source heat pumps (GSHP). However, the potential of SGE varies from region to region due to different geological conditions. There is a lack of regulations and codes for assessing SGE, which makes the design and planning of GSHP restricted. In this study, an evaluation system of the suitability of GSHP in a region of Qingdao by using Analytic Hierarchy Process (AHP) is proposed, and the test area is divided into three suitability levels based on suitability scores. The evaluation system contains property indicators, elemental indicators, and their weights. The result shows that the highly suitable area for the application of GSHP in the test area is 110.04 km2, accounting for 41.8% of the whole test area. The area of moderately suitable area is 65.02 km2, accounting for 24.7%, and GSHP should be developed and utilized on the basis of full demonstration in this level. The unsuitable area for GSHP is 88.19 km2, accounting for 33.5%. The indicator weights in this article may only be applicable to the Qingdao area and cities with similar geological conditions to Qingdao. However, the indicators within this evaluation system can be applied to the vast majority of locations where GSHP are to be developed, as it provides a method of assessment in terms of geological conditions, groundwater conditions, construction conditions, and ecological aspects.